Unmasking HAM/TSP: understanding HTLV-1-driven neurological disease - Arash Letafati; Saeed Tajik; Mona Vasei Rad; Ramin Shahbahrami; Melina Moulaeian; Mehdi Norouzi; Sayed-Hamidreza Mozhgani (Journal of NeuroVirology, 2026)

Non-point source pollution transport and photocatalytic degradation effect in the Mudong River basin of Huixian Wetland based on WASP model - Yiyang Li; Zitao Li; Junfeng Dai; Saeed Rad; Xiaolan Xie; Shanshan Qi; Baoli Xu (Environmental Monitoring and Assessment, 2025)

Postharvest UV-B and UV-C treatments combined with fermentation enhance the quality characteristics of Capparis spinosa L. fruit, improving total phenols, flavonoids, anthocyanins, phenolic acids, and antioxidant activity - Shima Babaei-Rad; Hasan Mumivand; Saeed Mollaei; Ali Khadivi (Food Chemistry, 2025)

Simultaneous removal of salt and dissolved petroleum compounds by a two-stage process: spiral wound capacitive deionization three-dimensional electro-Fenton - Saeed Tekyeh; Hasan Amini Rad; Daryoush Yousefi Kebria (Environmental Science and Pollution Research, 2025)

A review of the degradation of antibiotic contaminants using advanced oxidation processes: modification and application of layered double hydroxides based materials - Mingqi Xie; Chongmin Liu; Meina Liang; Saeed Rad; Zejing Xu; Shaohong You; Dunqiu Wang (Environmental Science and Pollution Research, 2024)

Self-assembled peptide/polymer hybrid nanoplatform for cancer immunostimulating therapies - Saeedeh Khazaei; Ruben Varela-Calviño; Mazda Rad-Malekshahi; Federico Quattrini; Safura Jokar; Nima Rezaei; Saeed Balalaie; Ismaeil Haririan; Noemi Csaba; Marcos Garcia-Fuentes (Drug Delivery and Translational Research, 2024)
Integrating peptide epitopes in self-assembling materials is a successful strategy to obtain nanovaccines with high antigen density and improved efficacy. In this study, self-assembling peptides containing MAGE-A3/PADRE epitopes were designed to generate functional therapeutic nanovaccines. To achieve higher stability, peptide/polymer hybrid nanoparticles were formulated by controlled self-assembly of the engineered peptides. The nanoparticles showed good biocompatibility to both human red blood- and dendritic cells. Incubation of the nanoparticles with immature dendritic cells triggered immune effects that ultimately activated CD8 + cells. The antigen-specific and IgG antibody responses of healthy C57BL/6 mice vaccinated with the nanoparticles were analyzed. The in vivo results indicate a specific response to the nanovaccines, mainly mediated through a cellular pathway. This research indicates that the immunogenicity of peptide epitope vaccines can be effectively enhanced by developing self-assembled peptide-polymer hybrid nanostructures. Graphical Abstract

Investigating Airborne Pollen Grains and Fungal Spores that Might be Related to Thunderstorm Asthma Attacks - Hassan Dehdari Rad; Heydar Maleki; Gholamreza Goudarzi; Mohammad-Ali Assarehzadegan; Ismaeil Idani; Ali Akbar Babaei; Abdolkazem Neisi; Saeed Jahantab; Mohammad Reza Parishani; Mehri Dinarvand; Armin Sorooshian; Foroogh Namjoyan; et al. (International Journal of Environmental Research, 2023)

A comprehensive review on pollution status and associated health risk assessment of human exposure to selected heavy metals in road dust across different cities of the world - Asfandyar Shahab; Zhang Hui; Saeed Rad; He Xiao; Jamil Siddique; Liang Liang Huang; Habib Ullah; Audil Rashid; Mohd Raihan Taha; Noor Zada (Environmental Geochemistry and Health, 2023)

Experimental and field studies on the behavior of drilled displacement piles - Saeed Hejazi Rad; Soheil Ghareh; Abolfazl Eslami; Navid Ganjian (Innovative Infrastructure Solutions, 2021)

Spatial and temporal variation of dissolved heavy metals in the Lijiang River, China: implication of rainstorm on drinking water quality - Liming Deng; Asfandyar Shahab; He Xiao; Jieyue Li; Saeed Rad; Jinping Jiang; GuoYu; Pingping Jiang; Hongwei Huang; Xiangkui Li; Bilal Ahmad; Jamil Siddique (Environmental Science and Pollution Research, 2021)

Otolith shape analysis and growth characteristics in larval and juvenile Squalidus argentatus - Ming Hui Gao; Zhi Qiang Wu; Liang Liang Huang; Xi Chang Tan; Hao Liu; Saeed Rad (Environmental Biology of Fishes, 2021)

Comparison of osteogenic differentiation potential of induced pluripotent stem cells and buccal fat pad stem cells on 3D-printed HA/β-TCP collagen-coated scaffolds - Sheida Hashemi; Leila Mohammadi Amirabad; Saeed Farzad-Mohajeri; Maryam Rezai Rad; Farahnaz Fahimipour; Abdolreza Ardeshirylajimi; Erfan Dashtimoghadam; Mohammad Salehi; Masoud Soleimani; Mohammad Mehdi Dehghan; Lobat Tayebi; Arash Khojasteh (Cell and Tissue Research, 2021)

Activities and polymorphisms of MMP-2 and MMP-9, smoking, diabetes and risk of prostate cancer - Amir Kiani; Marjan Kamankesh; Asad Vaisi-Raygani; Mahmoud-Reza Moradi; Maryam Tanhapour; Zohreh Rahimi; Saeed Elahi-Rad; Fariborz Bahrehmand; Mahdieh Aliyari; Faranak Aghaz; Hadi Mozafari; Nayebali Rezvani; et al. (Molecular Biology Reports, 2020)

Assimilation of exogenous cyanide cross talk in Oryza sativa L. to the key nodes in nitrogen metabolism - Cheng-Zhi Li; Li Yang; Yu-Juan Lin; Hua Zhang; Saeed Rad; Xiao-Zhang Yu (Ecotoxicology, 2020)

Elimination of Staphylococcus aureus nasal carriage in intensive care patients lowers infection rates - Leila Akhtar Danesh; Zeinab Saiedi Nejad; Hossein Sarmadian; Saeed Fooladvand; Alex van Belkum; Ehsanollah Ghaznavi-Rad (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

High prevalence of methicillin resistant and enterotoxin gene-positive Staphylococcus aureus among nasally colonized food handlers in central Iran - Saeed Fooladvand; Hossein Sarmadian; Danial Habibi; Alex van Belkum; Ehsanollah Ghaznavi-Rad (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

A Clinical and Molecular Genetic Study of 50 Families with Autosomal Recessive Parkinsonism Revealed Known and Novel Gene Mutations - Shaghayegh Taghavi; Rita Chaouni; Abbas Tafakhori; Luis J. Azcona; Saghar Ghasemi Firouzabadi; Mir Davood Omrani; Javad Jamshidi; Babak Emamalizadeh; Gholam Ali Shahidi; Mona Ahmadi; Seyed Amir Hassan Habibi; Azadeh Ahmadifard; et al. (Molecular Neurobiology, 2018)

Two-phase vesicles: a study on evolutionary and stationary models - MohammadMahdi Sahebifard; Alireza Shahidi; Saeed Ziaei-Rad (European Biophysics Journal, 2017)